1999
DOI: 10.1046/j.1460-2687.1999.00028.x
|View full text |Cite
|
Sign up to set email alerts
|

On the double pendulum model of the golf swing

Abstract: The primary aim of this computational study was to investigate the effect of positioning the ball so that contact between clubhead and ball takes place at the point in the downswing where the clubhead achieves its maximum horizontal component of velocity. The double pendulum model of the downswing was employed and computational results were obtained for a range of ‘release angles’ (the release angle determines the stage in the downswing at which the wrist joint is allowed to turn freely). The position of the w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
33
1

Year Published

2006
2006
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(36 citation statements)
references
References 7 publications
2
33
1
Order By: Relevance
“…For this reason, some previous studies have used clubhead speed as an indicator of optimised performance (e.g. Hume et al, 2005;Pickering & Vickers, 1999;White, 2006). Furthermore, it has been demonstrated that better golfers are indeed able to generate higher clubhead speeds (Bradshaw et al, 2009;Fradkin, Sherman, & Finch, 2004;Hocknell, 2002).…”
Section: Please Scroll Down For Articlementioning
confidence: 94%
“…For this reason, some previous studies have used clubhead speed as an indicator of optimised performance (e.g. Hume et al, 2005;Pickering & Vickers, 1999;White, 2006). Furthermore, it has been demonstrated that better golfers are indeed able to generate higher clubhead speeds (Bradshaw et al, 2009;Fradkin, Sherman, & Finch, 2004;Hocknell, 2002).…”
Section: Please Scroll Down For Articlementioning
confidence: 94%
“…A recurrent simplification in the golf swing literature has been the assumption that the downswing can be represented as a movement occurring in a single constant plane [3,[6][7][8][9][10][11][12][13][14][15][16]. However, there is research which suggests the downswing is not planar.…”
Section: Introductionmentioning
confidence: 99%
“…Since, others have concentrated on golf swing physics, ranging from planar rigid-link models [2][3][4][5][6][7][8] to three-dimensional kinematic analysis [9][10][11][12][13][14][15]. The objective of most studies is to study the effect of body segment rotation, or the applied torques generating segment rotation, on the performance of the golf swing, which was primarily characterised by club head velocity at impact.…”
Section: Introductionmentioning
confidence: 99%